Identification of B1 and SAG3 of Toxoplasma Gondii Genes in Breast Cancer Tissues Among Females in Kerbala Province, Iraq - Sabah Al-eadani, Aqala; A.M. Al-Mussawi, Kawther; Jabur Kehiosh, Haider (Pure Sciences International Journal of Kerbala, 2025)
The present investigation was done in November 2023. One hundred fifty specimens of malignant Breast cancer tissue, covered with paraffin wax and diagnosed by a specialist, have been gathered along with fifty specimens of benign tumour tissue. The control set was comprised of specimens taken from the histopathologist lab at Imam AL- Hussein Medical City (IHMC), the Al-Kafeel Spec Iality Hospital Lab (KSHL), and the Specialized Al-Sajjad Laboratory (SSL) for histopathology and tumour identification. The investigation contained two sets of specimens. The initial cohort comprised 66 females with breast carcinoma who did not receive chemotherapy, while the subsequent cohort included 84 females with breast carcinoma who did take chemotherapy. PCR technique was utilized on DNA from specimens of tissue afflicted by breast carcinoma across all studied sets, focusing on the amplification of the B1 and SAG3 genes.This work attempted to ascertain the prevalence of toxoplasmosis in patients with breast carcinoma. The toxoplasmosis incidence in patients with breast carcinoma was 11.3%, and the infection rate in normal participants was 4 percent. The data indicated that the infection rate among females who underwent therapy was higher than that of untreated females, attributable to their weakened immunity and increased infection risk, resulting in a 3.7 % greater probability of patients females acquiring breast carcinoma in comparison to normal females.